The Effect of Accounting Package Software ACOSYS Operator’s Ability to The Accounting Information Quality - Nikita Lapas Awdes; Rendra Trisyanto Surya (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Accounting in company nowdays have been helped by accounting package software which grows rapidly. The usage of the accounting package software provides many conveniences and can improve the generated accounting information quality. It is also possibile to be applied in MSMEs. However, it is feared that the limited number of employees and various level of competence in MSMEs could pose some risks to the generated information. Therefore, the purpose of this study is to determine the effect of accounting software operator’s competence on the accounting information quality at the MSME CV Putra Tunggal. The population of this study are the manager and employees of CV Putra Tunggal. The data method used in this study is a questionnaire and will use simple linear regression analysis. The results of this study indicate that the competence of the ACOSYS accounting software operator has a positive and significant effect on the accounting information quality.